EFFECT OF VANADIUM ON THE DEACTIVATION OF FCC CATALYSTS - Roncolatto,R.E (1998)
This work provides concrete evidence that vanadium causes the destruction of the zeolite in the FCC catalysts by a mechanism of acid attack or solid-solid transformation, as well as additional dealumination of the zeolite framework in the presence of steam and at high temperature. While these effects resulted in the reduction in crystallinity (zeolite Y content), specific area and unit cell size of the Y zeolite as the amount of vanadium in the catalysts increased, the reduction in activity was the most pronounced. The differences in these behaviors were interpreted and the model can be used for better catalyst formulation or screening.